Cardiac involvement in genotype-positive Fabry disease patients assessed by cardiovascular MR. Issue 4 (4th January 2016) - Kozor, Rebecca; Grieve, Stuart M; Tchan, Michel C; Callaghan, Fraser; Hamilton-Craig, Christian; Denaro, Charles; Moon, James C; Figtree, Gemma A
Abstract : Objective: Cardiac magnetic resonance (CMR) has the potential to provide early detection of cardiac involvement in Fabry disease. We aimed to gain further insight into this by assessing a cohort of Fabry patients using CMR. Methods/results: Fifty genotype-positive Fabry subjects (age 45±2 years; 50% male) referred for CMR and 39 matched controls (age 40±2 years; 59% male) were recruited. Patients had a mean Mainz severity score index of 15±2 (range 0–46), reflecting an overall mild degree of disease severity. Compared with controls, Fabry subjects had a 34% greater left ventricular mass (LVM) index (82±5 vs 61±2 g/m 2, p=0.001) and had a significantly greater papillary muscle contribution to total LVM (13±1 vs 6±0.5%, p<0.001), even in the absence of left ventricular hypertrophy (LVH). Late gadolinium enhancement (LGE) was present in 15 Fabry subjects (9/21 males and 6/23 females). The most common site for LGE was the basal inferolateral wall (93%, 14/15). There was a positive association between LVM index and LGE. Despite this, there were two males and three females with no LVH that displayed LGE. Of Fabry subjects who were not on enzyme replacement therapy at enrolment (n=28), six were reclassified as having cardiac involvement (four LVH-negative/LGE-positive, one LVH-positive/LGE-positive and one LVH-positive/LGE-negative). Conclusions: CMR was able to detect cardiac involvement in 48% of this Fabry cohort, despite the overall mild disease phenotype of the cohort. Of those not on ERT, 21% were reclassified as having cardiac involvement allowing improved risk stratification and targeting of therapy.